Altered Expression of IFN-λ2 in Allergic Airway Disorders and Identification of Its Cell Origins - Qiuli Wang; Dong Chen; Hua Xie; Xiaoping Lin; Xuefeng Wang; Qijian Yao; Xiaoxuan Zheng; Chiyan Xu; Lingfei Chen; Shaoheng He; Huiyun Zhang (Hindawi Limited, 2016)
This study investigated the expression levels of interferon- (IFN-) λ2 in peripheral blood and tissues. The results showed that the levels of IFN-λ2 were elevated by 17.9% and 14.2% in the plasma of allergic rhinitis (AR) and combined rhinitis with asthma (AR + AS), which was positively correlated with the level of tryptase but negatively correlated with the level of IL-10. IFN-λ2 was predominately expressed in the CD16+ cells and CD14+ cells in healthy control subjects (HC) but upregulated only in CD8+ cells of AR and in eosinophils of asthma. It was observed that approximately 6.6% and 7.0% dispersed tonsil cells and 5.8% and 0.44% dispersed lung cells are IFN-λ2+ mast cells and macrophages. Moreover, tryptase and agonist peptides of PAR-2 induced enhanced IFN-λ2 mRNA expression in A549 cells. In conclusion, the elevated levels of IFN-λ2 in the plasma of AR and AR + AS indicate that IFN-λ2 is likely to contribute to the pathogenesis of allergic airway disorders. The potential origins of the elevated plasma IFN-λ2 include mast cells, macrophages, and epithelial cells in tissues, neutrophils, monocytes, CD8+ T cells, and eosinophils in peripheral blood. Development of IFN-λ2 related therapy may help to treat or prevent allergic airway disorders.